Analisis Penyusunan Laporan Keuangan Masjid Dan Perlakuan Akuntansinya (Studi Kasus Pada Masjid Jami’baeturrahmah Cicadas) - Siti Nuridah; Listya Ningrum; Rudy Rahwana; Joelianti Dwi Supraptiningsih; Marisa Agustina (PT. ALHAFI BERKAH INDONESIA, 2024)
The mosque is a non-profit organization with the aim of serving the people and financial goals. These financial goals must not violate provisions prohibited by religious teachings. One effort to create good financial governance is to create good accountability by implementing accounting practices. The practice in question is the accounting and financial reporting treatment of mosques which needs to be adjusted to PSAK No. 45 so that financial reports are more relevant, easy to understand, reliable and comparable. However, most mosques still make financial reports in the form of two channels, namely income and expenditure. Therefore, the aim of this research is to reveal the management of the financial reports of the Jami' Baeturrahmah Cicadas Mosque based on PSAK No. 45. This research aims to find out how financial reports are prepared at the Jami' Baeturrahmah Cicadas Mosque. This is field research using qualitative research methods, the subject of this research is the manager of the Jami' Baeturrahmah Cicadas Mosque who knows best about recording financial reports. Data collection techniques in this research used observation, interview and documentation techniques. The data validation technique uses a credibility test with source triangulation. The results of this research indicate that 1) the management of financial reports at the Jami' Baeturrahmah Cicadas Mosque has managed, reported and disclosed all activities and activities related to the use of public resources well 2) Management has understood financial reports within the scope of worship organizations and the importance of recording reports finance, but the accounting treatment for recording financial reports is still made in the form of two channels, namely income and expenditure, so that not yet in accordance with PSAK No. 45. 3) Obstacles in implementing financial report recording based on PSAK 45 are lack of knowledge about how to prepare financial reports, lack of competent resources, lack of training or assistance from related parties, and no facilities in the form of a simple accounting program.